Behavior Based Access Control for Distributed Healthcare Environment - Yarmand, Hosein Mohammad (My University, 2008)
Sensitivity of clinical data and strict rules regarding data sharing have caused privacy and security to be critical requirements for using patient profiles in distributed healthcare environments. The amalgamation of new information technology with traditional healthcare workflows for sharing patient profiles has made the whole system vulnerable to privacy and security breaches. Standardization organizations are developing specifications to satisfy the required privacy and security requirements. In this thesis we present a novel access control model based on a framework designed for data and service interoperability in the healthcare domain. The proposed model for customizable access control captures the dynamic behavior of the user and determines access rights accordingly. The model is generic and flexible in the sense that an access control engine dynamically receives security effective factors from the subject user, and identifies the privilege level in accessing data using different specialized components within the engine. Standard data representation formats and ontologies are used to make the model compatible with different healthcare environments. The access control engine employs an approach to follow the user's behavior and navigates between engine components to provide the user 's privilege to access a resource. A simulation environment is implemented to evaluate and test the proposed model.
Keywords: Computing and Software